1996
DOI: 10.1159/000237398
|View full text |Cite
|
Sign up to set email alerts
|

IgE Levels, Atopy Markers and Hay Fever in Relation to Age, Sex and Smoking Status in a Normal Adult Swiss Population

Abstract: Within the framework of the SAPALDIA survey (Swiss study on Air Pollution and Lung Diseases in Adults), we studied the influence of sex, age and smoking habits on total serum IgE and allergen-specific IgE antibody concentrations (assessed by means of the Phadiatop® test) and on the prevalence of hay fever. A total of 8,344 subjects aged 18–60 years, comprising 2,776 current smokers, 1,888 former smokers and 3,680 nonsmokers, were included in the study. Smokers had both a statistically significant (p < 0.001) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
104
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 6 publications
17
104
1
Order By: Relevance
“…Increase in total IgE levels is associated with both smoking and atopy, but separately [18,19]. Atopic markers such as increased specific IgE levels and immediate skin reactivity to common inhalants seem to be even less common in smokers [20]. Smoking has however been found to be a determinant of IgE-mediated sensitization to such occupational agents as psyllium [21] and platinum salts [22].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in total IgE levels is associated with both smoking and atopy, but separately [18,19]. Atopic markers such as increased specific IgE levels and immediate skin reactivity to common inhalants seem to be even less common in smokers [20]. Smoking has however been found to be a determinant of IgE-mediated sensitization to such occupational agents as psyllium [21] and platinum salts [22].…”
Section: Discussionmentioning
confidence: 99%
“…In three studies, the prevalence of self-reported nasal allergy symptoms was lower in smokers than in nonsmokers (55,715,723). In one study involving adolescents, smoking was found to increase the prevalence of rhinoconjunctivitis (729).…”
Section: Pollutantsmentioning
confidence: 95%
“…These materials are typically burnt in simple stoves with a very incomplete combustion. Consequently, women and young children are exposed to high levels of indoor air pollution every day, resulting in an estimated 1.5-2.0 million premature deaths a year and a high prevalence of COPD (698,710 (712)(713)(714)(715)(716) and the IgE sensitization to some occupational allergens (717)(718)(719). However, in the absence of longitudinal studies, it is difficult to establish whether smoking is a causative factor of allergy or not (714,720).…”
Section: Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were classified as having elevated IgE level if their total IgE level was greater than or equal to 100 IU/mL per current interpretation of total serum IgE values in screening for atopic diseases in adults. 26,27 Selection and genotyping of SPP1 polymorphisms…”
Section: Study Populationmentioning
confidence: 99%